Legal Protection of Third Parties in Problematic Notarial Deeds Based on Law No. 2 of 2014 and the Civil Code - Salam, Ahmad Muhammad; Rokhyati, Sri; Samosir, Tetti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study aims to analyze the form of legal protection for third parties in problematic notarial deeds and to examine the extent of the notary's responsibility if the deed causes losses to parties other than the parties who appear directly. This problem is important to study considering that notarial deeds have perfect evidentiary power and can have broad legal consequences, including for third parties who are not directly involved in making them. The method used in this study is the normative legal method with a statutory approach and a case approach. Data were obtained through a literature study covering primary and secondary legal materials, and were analyzed qualitatively to interpret applicable legal provisions and their application practices in dispute resolution. The results of the study indicate that legal protection for third parties has not been explicitly regulated in Law No. 2 of 2014 concerning the Position of Notary or in the Civil Code. However, protection can be provided through the application of general principles in civil law such as good faith, the principle of prudence, and the principle of responsibility for unlawful acts. Notary liability can be requested if there is proven negligence in carrying out his/her duties that causes losses to third parties. This liability can be in the form of civil, administrative, or even criminal liability, depending on the form of violation committed. The conclusion of this study emphasizes the importance of strengthening regulations regarding notary liability and protection of third parties more firmly in laws and regulations. In addition, progressive legal interpretation is also needed from the judicial institution to ensure justice and legal certainty for all parties affected by the existence of notarial deeds.